Metformin‐Templated Nanoporous ZnO and Covalent Organic Framework Heterojunction Photoanode for Photoelectrochemical Water Oxidation. Issue 1 (27th October 2020) - Chatterjee, Sauvik; Bhanja, Piyali; Ghosh, Dibyendu; Kumar, Praveen; Kanti Das, Sabuj; Dalapati, Sasanka; Bhaumik, Asim
Abstract: Photoelectrochemical water‐splitting offers unique opportunity in the utilization of abundant solar light energy and water resources to produce hydrogen (renewable energy) and oxygen (clean environment) in the presence of a semiconductor photoanode. Zinc oxide (ZnO), a wide bandgap semiconductor is found to crystallize predominantly in the hexagonal wurtzite phase. Herein, we first report a new crystalline triclinic phase of ZnO by using N‐rich antidiabetic drug metformin as a template via hydrothermal synthesis with self‐assembled nanorod‐like particle morphology. We have fabricated a heterojunction nanocomposite charge carrier photoanode by coupling this porous ZnO with a covalent organic framework, which displayed highly enhanced photocurrent density of 0.62 mA/cm 2 at 0.2 V vs. RHE in photoelectrochemical water oxidation and excellent photon‐to‐current conversion efficiency at near‐neutral pH vis‐à‐vis bulk ZnO. This enhancement of the photocurrent for the porous ZnO/COF nanocomposite material over the corresponding bulk ZnO could be attributed to the visible light energy absorption by COF and subsequent efficient charge‐carrier mobility via porous ZnO surface. Abstract : Novel porous ZnO/COF: PEC OER : A new ZnO triclinic phase having nanoscale porosity is developed by using a well‐known drug molecule metformin as template and its coupling with a covalent organic framework results very good photocurrent density in photoelectrochemical water oxidation and excellent photon‐to‐current conversion efficiency at almost neutral pH conditions.